P1-S4.32 Recruiting via social networking sites for sexual health research (assessing chlamydia and HPV knowledge). (10th July 2011) - Garland, S M; Wark, J D; Tabrizi, S N; Jayasinghe, Y; Moore, E; Fletcher, A; Gunasekaran, B; Ahmed, N; Fenner, Y
Abstract : Background: Recruiting participants into population health studies has become increasingly challenging: traditional strategies have limitations including low participation rates and high costs. Social networking sites, commonly used for communication by young people, present an unique opportunity for innovative recruitment modalities. Method: This is part of a larger feasibility study assessing use of Facebook to recruit subjects for a novel prospective health study, the Young Female Health Initiative (YFHI). Women aged 16 to 25 years, living in Victoria, Australia were eligible to participate. An advertisement was placed on Facebook between May—and October 2010 and was visible to a random sample of eligible women. Women clicking on the advertisement were redirected to our website (http://www.yfhi.org ) and invited to provide their contact details. They were contacted by a researcher and asked to complete a survey at the YFHI study site, or to complete the questionnaire online. The survey contained demographic questions, plus sensitive questions about sexual history, experience and knowledge of Chlamydia trachomatis, human papillomavirus (HPV) and HPV vaccines. Results: 551 women responded to the advertisement (recruitment could be scaled up or down by changing the advertising frequency). We enrolled 426 respondents, of whom 278 completed the survey within the time available (50% at the study site, 50% online). Respondents' age and geographical distribution (urban, regional, rural) was representative of the target population; women over 18 years were 37% more likely to enrol and complete the survey than 16–17-year olds (p<0.05). Despite the sensitive nature of some questions, over 98% of participants found the survey not at all, or only slightly, embarrassing. Overall, 63% had heard of HPV: of these, 73% knew that HPV is sexually acquired and 94% knew that it causes cancer. 78% had heard of chlamydia: those who were sexually active were more likely to know of chlamydia than virgins (p<0.01), while 63% knew it could cause chronic pelvic pain, and 86% that it could cause infertility. This recruitment method also was cost-effective ($USD 20 per compliant participant). Conclusions: Results demonstrate excellent potential for such information and communication technologies (ICT) to engage young women in health research, including those from regional and rural communities, and support the use of ICT in future population-based studies, including sexual health research.